Design of Shielded Metal Arc Welding Parameters For Optimum Tensile Strength Using Taguchi Method - Setiawan, Moh. Dedy Indra; Pradana, Yanuar Rohmat Aji; Suprayitno, Suprayitno (Universitas Negeri Malang, 2021)
Shielded Metal Arc Welding (SMAW), an arc welding process, is widely used in applications. In practice, SMAW is widely applied to the welding process on hollow square pipe. Performance expected from this welding is the tensile strength of weld joint. The tensile strength is influenced by parameters process which have possibility for an optimization process to become ‘robust’. Robust is a design which less sensitive to the effect of uncertain quantities or noise factors. Taguchi method is the most efficient optimization method which accommodates the noise factors effect and requires less experiment. This study is focusing on optimizing the welding process on hollow square pipe. Parameters process such as welding current (I), electrode angle (θ), root gap (d) and electrode type (E) are adopted as parameters design. Taguchi method are chosen as a strategy and L9 fractional orthogonal array are chosen as the design experiment, which only 9 experiment samples needed from 81 experiments that should have been carried out for full factorial design. The objectivity is to maximize the tensile strength of weld joint. Three replications of L9 fractional orthogonal array Taguchi had been performed to generate the tensile strength and estimates the fluctuation of the output caused by noise factors. This study found that the welding current of 100A (I), electrode angle (θ) of 90°, root gap (d) of 2 mm, and electrode type (E) of E7018 produce the optimum results. Tensile strength improved from this robust parameter design is about 98.39 MPa based on initial parameter design.